Polymer electrolyte membrane fuel cell flow field designs and approaches for performance enhancement - Celik, Erman; Karagoz, Irfan (Sage Publications Ltd, 2020)
Polymer electrolyte membrane fuel cells are carbon-free electrochemical energy conversion devices that are appropriate for use as a power source on vehicles and mobile devices emerging with their high energy density, lightweight structure, quick startup and lower operating temperature capabilities. However, they need more developments in the aspects of reactant distribution, less pressure drops, precisely balanced water content and heat management to achieve more reliable and higher overall cell performance. Flow field development is one of the most important fields of study to increase cell performance since it has decisive effects on performance parameters, including bipolar plate, and thus fuel cell weight. In this study, recent developments on conventional flow field designs to eliminate their weaknesses and innovative design approaches and flow field architectures are obtained from patent databases, and both numerical and experimental scientific studies. Fundamental designs that create differences are introduced, and their effects on the performance are discussed with regard to origin, objective, innovation strategy of design besides their strength and probable open development ways. As a result, significant enhancements and design strategies on flow field designs in polymer electrolyte membrane fuel cells are summarized systematically to guide prospective flow field development studies.
Keywords: Polymer electrolyte membrane fuel cell; advanced flow field design; bioinspired flow field design